Colorblind Racial Ideology Is Associated with the Use of Race in Medical Decision‐Making. (15th September 2021) - Okah, Ebiere; Thomas, Janet; Westby, Andrea; Cunningham, Brooke
Abstract : Research Objective: Colorblindness is an ideology or worldview that minimizes the role of systemic racism in shaping outcomes for people of color and attributes racial disparities to the bad choices and poor behavior of racial minorities. Physicians who adhere to a color‐blind ideology may be less likely to critically interrogate the role of racism in shaping health outcomes, and, therefore, less likely to challenge race‐based treatment guidelines. The purpose of this study is to determine if colorblindness is associated with the use race in medical decision‐making. Study Design: This is a cross‐sectional analysis of survey data. Our online survey included demographic questions and two validated surveys: the Color‐blind Racial Attitudes Scale (CoBRAS) and the Racial Attributes in Clinical Evaluation (RACE) scale. CoBRAS measures colorblindness using three continuous subscales to measure respondents' unawareness of (1) racial privilege (scored 7–42); (2) institutional discrimination (scored 7–42) and blatant racial issues (scored 7–36). Higher scores indicate a lack of awareness and thus higher levels of colorblindness. The RACE scale (scored 0–28) was used to determine the extent to which physicians used race in medical management, with a higher score indicating a greater use of race. Multivariate regression analyses were used to assess the relationship between a color‐blind racial ideology and the use of race in medical decision making. Population Studied: In September 2019, the survey was sent to the 2039 members of the Minnesota Academy of Family Physicians (MAFP). MAFP membership includes active and retired family medicine physicians, family medicine residents, medical students and "other members" (honorary, inactive and supporting members). Only family medicine physicians and residents completed the survey. Principal Findings: Our response rate was 14% (267/2039). Higher CoBRAS scores were associated with an increased use of race (β = 0.05, p < 0.01), after controlling for physician age, gender, race, location of training and practice characteristics. Of the three CoBRAS subscales, only unawareness of institutional discrimination was significantly associated with an increased use of race (β = 0.18, p = 0.01), after controlling for the aforementioned covariates. Additionally, physicians under 40 years of age, who worked in urban clinics, or had a clinic population consisting of at least 70% racial/ethnic minorities were significantly less likely to use race in their treatment decisions than physicians who were 40 years of age and older, worked in rural clinics, or had a clinic a population consisting of less than 30% racial/ethnic minorities, respectively. Conclusions: Physicians who adhere to a color‐blind racial ideology, particularly those who deny institutional racism, are more likely to use race in their screening and treatment decisions. Implications for Policy or Practice: In July 2020, American Academy of Family Physicians adopted a policy advising against the use of race in medical decision‐making. As the use of race may be due to colorblind racial ideology, and therefore due to a poor understanding of how systemic racism affects health, more physician education about racism as a health risk is needed. Additional research is also needed to evaluate physician motivations and beliefs as it relates to race‐based medical guidelines and policies. Primary Funding Source: Minnesota Academy of Family Physicians.